2014
DOI: 10.1371/journal.pone.0088397
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Characteristics of Immune-Related MicroRNAs in Haemocytes of Oyster Crassostrea gigas

Abstract: BackgroundMicroRNAs (miRNAs) represent a class of small ncRNAs that repress gene expression on the post-transcriptional level by the degradation or translation inhibition of target mRNA.MethodologyThree small RNA libraries from oyster haemocytes were sequenced on the Illumina platform to investigate the latent immunomodulation of miRNAs after bacteria challenge and heat stress. Totally, 10,498,663, 8,588,606 and 9,679,663 high-quality reads were obtained in the control, bacteria and bacteria+heat library, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 50 publications
4
42
1
Order By: Relevance
“…MicroRNAs (miRNAs) are 20-22 nt non-coding RNAs that play an important role in the regulation of many biological processes, such as signal transduction, organ development, cellular proliferation, apoptosis, oncogenesis, and immunity (Ma et al 2012;Zhou et al 2014;Nilsen 2007;Yang et al 2013;Pushpavalli et al 2014). In animals, miRNAs regulate their target genes through mRNA destabilization and translational inhibition (Bushati and Cohen 2007).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are 20-22 nt non-coding RNAs that play an important role in the regulation of many biological processes, such as signal transduction, organ development, cellular proliferation, apoptosis, oncogenesis, and immunity (Ma et al 2012;Zhou et al 2014;Nilsen 2007;Yang et al 2013;Pushpavalli et al 2014). In animals, miRNAs regulate their target genes through mRNA destabilization and translational inhibition (Bushati and Cohen 2007).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In previous studies, some immune-responsive miRNAs were identified in oysters [27] and were reassessed here for their involvement in expressional modulation of CgCTL1. As a result, the miRNA cgi-miR-2d increased significantly during V. splendidus challenge, and was predicted to target CgCTL1 via the 3′-UTR region [27].…”
Section: Discussionmentioning
confidence: 90%
“…Small RNAs are important regulators of the gene expression, as recognized in various model and nonmodel organisms (Kim Myung-Chul et al 2014;Martini et al 2014;Hussain and Asgari 2014;Sahoo et al 2014;Britton et al 2014;Poole et al 2014;Solofoharivelo et al 2014), including some bivalves (Jiao et al 2014;Zhou et al 2014). In addition to the identification of miRNAs, a general comprehension of the miRNA biogenesis in itself is also significant (Grimson et al 2008;Wu et al 2011;Moran et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The basic set of genes involved in the miRNA biogenesis, and related protein interactions, are well known in mammals (Lau and MacRae 2009), and also in other metazoans like Cnidaria (Moran et al 2013), Platyhelminthes (Resch and Palakodeti 2012) and insects (Lucas and Raikhel 2013;Hussain and Asgari 2014). Regarding mollusks, lists of miRNAs have been reported for a few species (Jiao et al 2014;Chen et al 2014;Martín-Gómez et al 2014;Zhou et al 2014), miRNA families have been investigated in the limpet genome (Kenny et al 2015) and one study has considered bivalve DICER sequences for phylogenetic analysis (Gao et al 2014). A general overview on the bivalve miRNA biogenesis complements is still lacking, so we took advantage of several genomic and transcriptomic datasets available for Lophotrochozoa (GIGA Community of Scientists et al 2014) to identify and characterize the core elements involved in the miRNA formation pathway in Mytilus and Crassostrea spp.…”
Section: Introductionmentioning
confidence: 99%